Efektifitas Penggunaan Hotpack dengan Selimut Tebal terhadap Grade Shivering - Dwi Handoyo; Nabhani Nabhani; Arimbi Aulia (Jurnal Sains dan Kesehatan, 2022)
Shivering a complication that often occurs due to spinal anesthesia, due to postoperative hypothermia. Risk factors shivering include: age, weight, operating room temperature and anesthetic drugs. One of the nonpharmacologi was to reduce grade shivering is by giving hot packs and thick blankets to samples with temperatures < 35.5⁰C. This research to determine the effectiveness comparison between use of hot packs and thick blankets. The design Quasi Experiment with post test control group design. The population all post spinal anesthesia shivering patients in the IBS Recovery Room of RST Slamet Riyadi. The sample are 2 groups,shivering patient with hotpack treatment and shivering patient with thick blanket controls. The sample 32 respondents, 16 respondents treatment group and 16 respondents control group. Data analysis Mann Whitney statistical test. The results showed that p value = 0.008 < α = 0.05 ,that H0 is rejected Ha is accepted, that difference in the effectiveness of using hot packs with thick blankets on grade shivering in post spinal anesthesia patients in the recovery room.